Comparison of In Vitro Endocrine Activity of Phthalates and Alternative Plasticizers - Hélène Moche; Aouatif Chentouf; Sergio Neves; Jean-Marc Corpart; Fabrice Nesslany (Journal of Toxicology)
Because of the deleterious effects of phthalates, regulations have been taken to decrease their use, and the needs for alternatives are increasing. Due to the concerns about the endocrine-disrupting properties of phthalates, it was deemed necessary to particularly investigate these effects for potential substitutes. In this study, we compared the in vitro endocrine activity of several already used potential alternative plasticizers (DEHT, DINCH, and TOTM) or new substitutes (POLYSORB® isosorbide and POLYSORB® ID 46) to one of 2 phthalates, DEHP and DINP. Effects of these chemicals on 3 common mechanisms of endocrine disruption, i.e., interaction with estrogen receptors (ER), androgen receptors (AR), or steroidogenesis, were studied using extensively used in vitro methods. In the E-Screen assay, only DEHP moderately induced MCF-7 cell proliferation; none of the other tested substances were estrogenic or antiestrogenic. No androgenic or antiandrogenic activity in MDA-kb2 cells was shown for any of the tested phthalates or alternatives. On the other hand, both DEHP and DINP, as well as DEHT, DINCH, and TOTM, disrupted steroidogenesis in the H295R assay, mainly by inducing an increase in estradiol synthesis; no such effect was observed for POLYSORB® isosorbide and POLYSORB® ID 46.